Complete nucleotide sequence and coding strategy of rice hoja blanca virus RNA4 - Ramírez, B.C.; Lozano Potes, Iván; Constantino, LM; Haenni, AL (Microbiology Society, 1993)
The complete sequence office hoja blanca virus (RHBV) RNA4 has been determined, based on the sequence of the corresponding eDNA clones. RNA4 consists of 1991 nucleotides with two open reading frames (ORFs). One putative ORF is located in the 5'-proximal region of the viral RNA4; it encodes a protein of predicted M r 20076 which corresponds to the major non-structural protein that accumulates in RHBV-infected rice plants, and which bears limited sequence identity with the helper component of tobacco vein mottling potyvirus. The other ORF is located in the 5'-proximal region of the viral complementary RNA4 and encodes a protein of predicted M r 32469. Between the two ORFs is an intergenic region of 524 nucleotides, part of which can theoretically adopt a stable stem-loop structure; the 5' and 3' ends can potentially base-pair over 16 nucleotides, producing a pan-handle configuration. These characteristics are in favour of an ambisense coding strategy for RHBV RNA4.